2014
DOI: 10.3762/bjnano.5.174
|View full text |Cite
|
Sign up to set email alerts
|

Different endocytotic uptake mechanisms for nanoparticles in epithelial cells and macrophages

Abstract: SummaryPrecise knowledge regarding cellular uptake of nanoparticles is of great importance for future biomedical applications. Four different endocytotic uptake mechanisms, that is, phagocytosis, macropinocytosis, clathrin- and caveolin-mediated endocytosis, were investigated using a mouse macrophage (J774A.1) and a human alveolar epithelial type II cell line (A549). In order to deduce the involved pathway in nanoparticle uptake, selected inhibitors specific for one of the endocytotic pathways were optimized r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
285
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(308 citation statements)
references
References 64 publications
21
285
1
1
Order By: Relevance
“…Three inhibitors were applied in these experiments. 24,25 Chlorpromazine (cpz) inhibits clathrin-mediated endocytosis. Methyl-β-cyclodextrin (mβcd) specifically inhibits clathrin-as well as caveolinmediated endocytosis.…”
Section: Uptake Mechanisms For Haps In Huvecsmentioning
confidence: 99%
“…Three inhibitors were applied in these experiments. 24,25 Chlorpromazine (cpz) inhibits clathrin-mediated endocytosis. Methyl-β-cyclodextrin (mβcd) specifically inhibits clathrin-as well as caveolinmediated endocytosis.…”
Section: Uptake Mechanisms For Haps In Huvecsmentioning
confidence: 99%
“…27,28 In addition, uptake mechanisms of NPs were reportedly dependent on the cell types. 29,30 In an earlier study, chitosan-conjugated AuNPs demonstrated endocytotic uptake in lung cancer cells. 25 In order to identify uptake of chitosan-conjugated AuNPs in hADMSCs, internalized chitosan-conjugated AuNPs were measured using a TEM.…”
Section: Uptake Of Chitosan-conjugated Aunps In Hadmscsmentioning
confidence: 99%
“…37 However, we found that cpz inhibited the uptake of m-HAP; furthermore, elegant experiments have demonstrated that NPs below 60 nm could also enter cells via clathrin-mediated endocytosis. 16,39 In summary, these findings indicate that the size of clathrin-coating vesicles might be outside the range of 150-200 nm. Given the complexity and diversity of uptake routes available in different cells, here, we explored only three main endocytic modes of these pathways.…”
mentioning
confidence: 99%
“…16,17 Chlorpromazine (cpz) was used to inhibit clathrin-mediated endocytosis. Inhibitions of clathrin-as well as caveolin-mediated endocytosis in hWJ-MSCs were tested via methyl-β-cyclodextrin (mβcd).…”
Section: Uptake Mechanisms For Haps In Hwj-mscsmentioning
confidence: 99%
See 1 more Smart Citation